Flexible glue material with PCO-resistant characteristic and application thereof
The soft glue material with anti-PCO properties prepared by synthesizing functional monomers and macromonomers and photocuring cross-linking technology solves the problem that existing IOL products are prone to PCO after surgery, and realizes the mechanical strength of the material and The improvement of optical performance extends service life and provides better visual quality.
Patent Information
- Application Number
- CN202411303913.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-11
AI Technical Summary
Existing IOL products for cataract surgery are prone to postoperative cataract (PCO) after surgery, and the refractive performance cannot be adjusted, resulting in a decrease in visual quality and the service life is no more than ten years.
A soft glue material with anti-PCO properties prepared by synthesizing functional monomers and macromonomers combined with photocuring crosslinking technology is used. This material introduces crosslinkable groups, refractive index regulator groups, and anti-cell adhesion and anti-cell adhesion. The groups deposited by proteins ensure the mechanical strength and optical properties of the material.
This material can effectively avoid the occurrence of PCO, extend the service life, provide better visual quality, and provide continuous zoom dynamic adjustment function for patients with presbyopia.
Smart Images

Figure CN119409975A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soft-gel intraocular lenses, and in particular to a soft-gel material with anti-PCO properties and application thereof. Background Art
[0002] Cataract is a common blinding disease caused by the opacity of the intraocular refractive medium lens, which reduces its transparency and causes vision loss. It is the leading cause of blindness in my country. Phacoemulsification combined with IOL implantation is the preferred surgical procedure for treating cataracts, which uses ultrasonic energy to emulsify the cloudy lens nucleus and cortex, remove them, retain the lens capsule, and implant a replacement IOL.
[0003] At present, artificial lens materials are mostly synthetic polymers, mainly including four categories: polymethyl methacrylate (PMMA), silicone, hydrogel and acrylic. These IOL products are all pre-formed lenses, which usually require a larger surgical incision of 3mm to 6mm. In addition, as the only refractive medium with adjustment ability in the eye's refractive system, whether the refractive performance of the IOL is adjustable is the key to the development of IOL products. The above IOL products have no adjustment function or limited adjustment function (<2D), which cannot meet the requirements of patients with different needs for higher visual quality after surgery. In addition, the "acrylate" IOLs widely used in the market have poor biocompatibility, potential toxicity, and no biological resistance (such as anti-protein deposition, anti-cell adhesion, etc.). During the postoperative wound healing reaction, the residual lens epithelial cells (LEC) will undergo potential proliferation and migration and adhere to the surface of the IOL. At the same time, the deposition of proteins on the surface of the IOL will cause the transparency of the lens to decrease, and ultimately lead to light scattering and decreased visual quality. This phenomenon is called Posterior Capsule Opacification (PCO). The incidence of PCO in IOL products currently used in clinical practice is relatively high, resulting in a service life of no more than ten years. Therefore, the development and use of soft rubber materials with anti-PCO properties are of great significance and have broad application prospects. Summary of the invention
[0004] In order to solve the defects of the prior art, the present invention provides a soft gel material with anti-PCO properties and its application, which solves the problem of post-opioid cataract (PCO) existing in IOLs used in cataract surgery and provides a continuous zoom dynamic adjustment function for presbyopic patients.
[0005] The technical solution adopted by the present invention is: a soft rubber material with anti-PCO characteristics, the soft rubber material is prepared by the following steps; (1) Synthesis of functional monomer: tetramethylcyclotetrasiloxane D4 with active hydrogen H The allyl functional group reacts with the catalysis of Karstedt's Pt catalyst to introduce the required functional group R and obtain the functional monomer D4. R ; (2) Synthesis of functional macromonomer: Octamethylcyclotetrasiloxane D4 and functional monomer D4 R Mixing with a capping agent in a mixed solvent of xylene and acetonitrile, reacting under the catalysis of TfOH acid, to obtain a functional macromolecular monomer, wherein the end group molecule is used to control the molecular weight and viscosity of the polymer, that is, the suitable injection degree; (3) Photocuring cross-linking: Mix the functional macromolecular monomer and the photoinitiator to cross-link to obtain a colorless or slightly yellow transparent soft glue.
[0006] The functional group R is one or more of a cross-linkable group, a refractive index regulating group, an anti-cell adhesion group and an anti-protein deposition group.
[0007] The cross-linkable group is one or more of methacrylates, acrylates, methacrylamides, acrylamides, and olefin double bonds.
[0008] The refractive index regulating group and the anti-protein deposition and anti-cell adhesion groups are one or more of polyvinyl alcohol, polyethylene glycol monohydroxy ether, polyethylene glycol monomethyl ether, trifluoromethyl and short-chain alcohol.
[0009] The functional macromolecular monomer has a molecular weight of 15-100 kDa and a viscosity range of 0.6-4 kPa.s.
[0010] The molar percentage of the cross-linkable groups to the functional macromolecular monomer access groups is 0.5-5%, so as to ensure that the modulus of the cross-linked soft rubber material is below 5KPa.
[0011] The molar percentage of the refractive index regulating group and the anti-protein deposition and anti-cell adhesion groups in the functional macromolecular monomer access group is 40-99.5%, and the refractive index RI is controlled in the range of 1.42-1.46, with the optimal range of 1.43-1.45 (n 37 D).
[0012] In the step (3), the photoinitiator for photoinitiated crosslinking is Irgacure 819 photoinitiator, the light source is 400-500nm blue light, and the light intensity is controlled at 50-200mW / cm 2 The cross-linking reaction time is less than 8 minutes, so the mechanical strength and optical properties of the synthesized material are close to those of natural lenses of young people.
[0013] A soft gel material with anti-PCO properties is used in the preparation of artificial lens materials.
[0014] The artificial lens material is prepared by injecting a mixture of a functional macromolecular monomer and a photoinitiator into a cleaned lens capsule and using a wavelength of 400-500nm and a light intensity density of 50-200mW / cm in the eye capsule. 2 Irradiate with blue light for 2-8 minutes to complete cross-linking and curing, and replace and substitute the diseased cataract lens.
[0015] The beneficial effects of the present invention are as follows: the present invention provides a soft gel material with anti-PCO properties and its application, and provides a "soft gel type IOL material" that is injectable, adaptable to minimally invasive surgery, has infinitely variable focus capability and biological resistance. The material precursor can be injected into the intraocular capsule through a syringe, with a very small implantation wound, and cross-linked into a soft gel in situ in the eye capsule, which mimics the performance of the natural lens of young people, allowing cataract patients to restore their natural accommodation function after surgery. The implanted soft gel has the properties of anti-cell adhesion and anti-protein deposition, which avoids the occurrence of PCO, has a longer service life than existing IOL products, and provides patients with better visual quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the synthetic route of the product of the present invention.
[0017] Figure 2 is the linear relationship between the refractive index and the mol% of PEG groups in the polymer.
[0018] Figure 3 This is a rheological test curve of the sample, where the initial viscosity η is 1.6 Pa.s and the storage modulus G′ after cross-linking is 1650 Pa.
[0019] Figure 4 The relationship between the modulus G′ and the curing time of samples with different cross-linking group contents.
[0020] Figure 5 This is the product transmittance test result (with UV protection effect).
[0021] Figure 6 is the relationship between the amount of PEG groups connected and the contact angle.
[0022] Figure 7 The product has anti-cell adhesion and proliferation properties.
[0023] Figure 8 The product has anti-bacterial adhesion and proliferation properties.
[0024] Fig. 9 The product has anti-protein adsorption and deposition properties.
[0025] Fig.10 This is a product cytotoxicity test. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 (1) Synthesis of functional monomers Add small molecule functional group reactants (1.1-1.2 molar equivalents) and 2-4 times the volume of xylene / acetonitrile mixed solvent into the reactor, then add a certain amount of Karstedt's Pt catalyst, under continuous N2 atmosphere protection and 55°C, use a syringe pump to slowly and evenly drop tetramethylcyclotetrasiloxane D4H-xylene solution with active hydrogen into the reactor at a rate of 20 mL / h in a precisely controllable manner, stabilize for 2 hours after the dropwise addition is completed, and then the reaction is terminated, add a certain amount of activated carbon to the reactor, stir overnight at room temperature and air atmosphere to decolorize (adsorb and remove the Karstedt's Pt catalyst that has been inactivated during the reaction process), use a suction filtration device to reduce pressure to filter out the activated carbon powder, and carry out high vacuum vacuum distillation and rotary distillation at 75-80°C for 20-30 minutes to obtain a functional monomer D4R with a purity greater than 98wt%, add a desiccant, and put it in a refrigerator at 4-8°C for refrigeration for subsequent synthesis.
[0028] Table 1. Synthesis of functional monomer D4R
[0029] Note: 1) AMA: Allyl methacrylate 2) APEG: Polyethylene glycol allyl methyl ether 3) AO: methallyl alcohol (2) Synthesis of functional macromonomers Add 39.5 parts of octamethylcyclotetrasiloxane (D4), functional monomers (D4R1, D4R2, D4R3), about 60 parts in total, and 0.5 parts of hexaethyldisiloxane (HEDS) to the reactor, add an equal volume of xylene and acetonitrile mixed solvent, and stir evenly. Under continuous N2 atmosphere protection and 35°C, after N2 stripping for 10 minutes, add a certain amount of trifluoromethanesulfonic acid (TfOH) catalyst to the reactor to start the reaction, and stop the reaction after 24 hours. Open the reactor, add excess Na2CO3 particles to the reactor, neutralize TfOH to neutrality, remove Na2CO3 solid particles by vacuum filtration, and distill under reduced pressure at 75°C for 20 minutes. After distilling out about 90% of xylene and acetonitrile solvents, transfer the product to a dialysis device, use ethanol as the solvent, and dialyze repeatedly 3-5 times to remove unreacted raw materials and small molecular monomers to obtain a functional macromolecular monomer and ethanol mixed solution. The mixed solution was poured into a round-bottom flask and more than 95% of the ethanol solvent was removed by rotary distillation under reduced pressure. The concentrated sample was then transferred to a sample bottle and placed in a vacuum oven at 40°C under vacuum conditions for 24 hours to remove the residual ethanol.
[0030] Table 2. Synthesis of functional macromonomers
[0031] Note: 1) R1 is a cross-linking group, 2) R2 is a bio-resistance group, etc.
[0032] (3) Preparation of light-cured samples A certain amount of freeze-dried functional macromolecular monomer was accurately weighed and placed in a reaction bottle, 0.22 wt% of Irgacure 819 photoinitiator was added, and then a certain amount of CHCl3 solvent was added. After stirring and mixing evenly in the dark, the CHCl3 solvent was removed by vacuum rotary evaporation at 35°C for 30 minutes to obtain a light yellow, clear, transparent, viscous liquid.
[0033] Finally, fill 2 mL of the product into a glass syringe needle wrapped in tin foil, remove all bubbles, seal with plastic, sterilize at 121°C for 30 min, and refrigerate for later use.
[0034] (4) Use of the product Before use, the product needs to be rewarmed for 15-20 minutes; during the operation, the product is injected into the cleaned lens capsule, and the operation process needs to be performed carefully and slowly to avoid the generation of bubbles and the outflow of colloid. After the artificial lens is filled, it is irradiated with blue light with a wavelength of 400-500nm and a light intensity density of 50-200mW / cm2 for 2-8 minutes to complete the curing and cross-linking.
[0035] Table 3. Comparative test of biological resistance of materials
[0036] Example 2 Relationship between the amount of PEG groups inserted and the contact angle The results are as follows Figure 6 As shown in the figure, with the increase of PEG content, the hydrophilicity gradually increased and the contact angle gradually decreased.
[0037] Example 3 The anti-cell proliferation and adhesion properties of the product prepared in Example 1 were verified. Figure 7 As shown, cell adhesion showed a trend of gradually decreasing with increasing PEG content (L929 cells).
[0038] Example 4 The antibacterial adhesion and proliferation performance of the product prepared in Example 1 was verified, and the results were as follows Figure 8 As shown, there was no obvious bacterial adhesion at 20%, 40%, 60%, 70%, 80%, and 95% PEG contents.
[0039] Example 5 Verify the anti-protein adsorption and deposition performance of the product prepared in Example 1. The results are as follows Fig. 9 As shown, it has good anti-protein adsorption and deposition performance.
[0040] Example 6 Cytotoxicity Experiment The results are as follows Fig.10 As shown, all silicone materials containing PEG had no potential cytotoxicity.
[0041] in conclusion The organosiloxane material with anti-PCO property and the artificial lens material prepared by the present invention are imitating the natural lens of young people and have the function of infinitely variable focus adjustment; the functional group of anti-secondary ophthalmopathy is introduced to extend the service life; the raw material cost is low and the intermediate preforming process is omitted, thus saving costs; the surgical process can use the existing technology without the need to introduce new operating equipment; the surgical incision is smaller and the patient recovers quickly.
[0042] Technical personnel should note that although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.
[0043] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A soft rubber material with anti-PCO properties, characterized in that: The soft rubber material is prepared by the following steps: (1) Synthesis of functional monomer: tetramethylcyclotetrasiloxane D4 with active hydrogen H React with the allyl functional group under the catalysis of Karstedt's Pt catalyst to introduce the required functional group R and obtain the functional monomer D4 R ; (2) Synthesis of functional macromonomer: Octamethylcyclotetrasiloxane D4 and functional monomer D4 R Mixing with a capping agent in a mixed solvent of xylene and acetonitrile, reacting under the catalysis of TfOH acid, to obtain a functional macromolecular monomer, wherein the end group molecule is used to control the molecular weight and viscosity of the polymer, that is, the suitable injection degree; (3) Photocuring crosslinking: Mix the functional macromolecular monomer with the photoinitiator and crosslink with blue light to obtain a colorless or slightly yellow transparent soft glue.
2. The soft rubber material with anti-PCO properties according to claim 1, characterized in that: The functional group R is one or more of a cross-linkable group, a refractive index regulating group, an anti-cell adhesion group and an anti-protein deposition group.
3. The soft rubber material with anti-PCO properties according to claim 2, characterized in that: The cross-linkable group is one or more of methacrylates, acrylates, methacrylamides, acrylamides, and olefin double bonds.
4. The soft rubber material with anti-PCO properties according to claim 2, characterized in that: The refractive index regulating group, anti-cell adhesion and anti-protein deposition group are one or more of polyvinyl alcohol, polyethylene glycol monohydroxy ether, polyethylene glycol monomethyl ether, trifluoromethyl and short-chain alcohol.
5. The soft rubber material with anti-PCO properties according to claim 2, characterized in that: The functional macromolecular monomer has a molecular weight of 15-100 kDa and a viscosity range of 0.6-4 kPa.s.
6. The soft rubber material with anti-PCO properties according to claim 3, characterized in that: The molar percentage of the cross-linkable groups to the functional macromolecular monomer access groups is 0.5-5%.
7. The soft rubber material with anti-PCO properties according to claim 4, characterized in that: The molar percentage of the refractive index regulating group and the anti-protein deposition and anti-cell adhesion group in the functional macromolecular monomer access group is 40-99.5%.
8. The soft rubber material with anti-PCO properties according to claim 1, characterized in that: In the step (3), the photoinitiator used for photoinitiated crosslinking is Irgacure 819 photoinitiator, the light source is 400-500nm blue light, and the light intensity is controlled at 50-200mW / cm 2 , the cross-linking reaction time is less than 8min.
9. Application of a soft gel material with anti-PCO properties in the preparation of artificial lens materials.
10. The use according to claim 9, characterized in that: The artificial lens material is prepared by injecting the prepared functional macromolecular monomer and photoinitiator mixture into the cleaned lens capsule and using a wavelength of 400-500nm and a light intensity density of 50-200 mW / cm in the eye capsule. 2 Irradiate with blue light for 2-8 minutes to complete cross-linking and curing, and replace and substitute the diseased cataract lens.
Citation Information
Patent Citations
Surface silicon-hydrogen functionalization silicone rubber material as well as preparation, hydrophilic treatment and application method
CN109575610A
Siloxane flexible soft rubber and application thereof
CN117736389A
Cited By
Soft gel material having Anti-PCO properties and use thereof
WO2026061380A1